2019
DOI: 10.1038/s41598-019-54041-0
|View full text |Cite
|
Sign up to set email alerts
|

Myotonia in a patient with a mutation in an S4 arginine residue associated with hypokalaemic periodic paralysis and a concomitant synonymous CLCN1 mutation

Abstract: The sarcolemmal voltage gated sodium channel NaV1.4 conducts the key depolarizing current that drives the upstroke of the skeletal muscle action potential. It contains four voltage-sensing domains (VSDs) that regulate the opening of the pore domain and ensuing permeation of sodium ions. Mutations that lead to increased NaV1.4 currents are found in patients with myotonia or hyperkalaemic periodic paralysis (HyperPP). Myotonia is also caused by mutations in the CLCN1gene that result in loss-of-function of the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…However, in both Ile215Thr and Gly241Val mutants, the shift in the voltage dependence of activation toward hyperpolarized potentials also accelerated the rate of the open-state inactivation, a mechanism consistent with a loss-of-function effect. This characteristic has already been observed by Petitprez et al ( 10), but has not been described for other mutants (13,14), which anyway showed a similar left shift for the voltage dependence of activation.…”
Section: Discussionsupporting
confidence: 69%
“…However, in both Ile215Thr and Gly241Val mutants, the shift in the voltage dependence of activation toward hyperpolarized potentials also accelerated the rate of the open-state inactivation, a mechanism consistent with a loss-of-function effect. This characteristic has already been observed by Petitprez et al ( 10), but has not been described for other mutants (13,14), which anyway showed a similar left shift for the voltage dependence of activation.…”
Section: Discussionsupporting
confidence: 69%
“…VI: 3 was affected with concomitant mutations in both the CLCN1 and SCN4A genes. Other researchers have also reported a few patients with the same genes mutated (Table 3) [15][16][17][18]. These patients showed an atypical phenotype, suggesting that concomitant mutations may act synergistically to influence the phenotype [19].…”
Section: Discussionmentioning
confidence: 87%
“…It is worthy to note that reports have been published regarding patients carrying both CLCN1 and SCN4A mutations or in concomitance with myotonic dystrophy nucleotide repeats, which may increase further the complexity of treatment [3,[92][93][94][95][96][97][98][99].…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In addition, another mechanism is likely involved in the pathogenesis of hypoPP, which is the creation of an aberrant gating pore [178][179][180]. Such gating pore has been found to occur in most hypoPP channel mutants [99,[181][182][183][184][185][186], and allows small leakage cationic currents at resting membrane potential that facilitates the paradoxical depolarization at low [K + ] causing muscle weakness [15].…”
Section: Preclinical Studiesmentioning
confidence: 99%